Professional development - Zambrano-Silva, Salvador (Anuario ThinkEPI, 2008)
Many different situations and factors can be obstacles to the professional growth of those who manage information and documentation. Some proposals are presented to try to surmount them, based on an analysis of selected messages from the IweTel professional list and personal reflections on the topic. The aim is to help sort out all the obstacles that we are presented with.